2014
DOI: 10.1128/jvi.02437-14
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Short Telomeric Repeat Region in Marek's Disease Virus Replication, Genomic Integration, and Lymphomagenesis

Abstract: Marek's disease virus (MDV) is a cell-associated alphaherpesvirus that causes generalized polyneuritis and T-cell lymphomas in chickens. MDV is able to integrate its genome into host telomeres, but the mechanism of integration is poorly understood. The MDV genome harbors two arrays of telomeric repeats (TMR) at the ends of its linear genome: multiple telomeric repeats (mTMR), with a variable number of up to 100 repeats, and short telomeric repeats (sTMR), with a fixed number of 6 repeats. The mTMR have recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…ic repeats [Kaufer et al, 2011;Greco et al, 2014]. In the MDV infection cycle, oncogenic strains transition from a cytolytic replication stage, during which the viral genome takes an episomal and extrachromosomal form, to a latent stage, characterized by evasion of host immune responses Adldinger and Calnek, 1973;Baigent and Davison, 2004;Osterrieder et al, 2006;Arumugaswami et al, 2009;Gimeno et al, 2011] with the latter having a temporal overlap with MDV-host telomere integration events [Robinson et al, 2010[Robinson et al, , 2014 and decline in the quantity of extrachromosomal MDV genomes [Kaschka-Dierich et al, 1979;Delecluse and Hammerschmidt, 1993].…”
mentioning
confidence: 99%
“…ic repeats [Kaufer et al, 2011;Greco et al, 2014]. In the MDV infection cycle, oncogenic strains transition from a cytolytic replication stage, during which the viral genome takes an episomal and extrachromosomal form, to a latent stage, characterized by evasion of host immune responses Adldinger and Calnek, 1973;Baigent and Davison, 2004;Osterrieder et al, 2006;Arumugaswami et al, 2009;Gimeno et al, 2011] with the latter having a temporal overlap with MDV-host telomere integration events [Robinson et al, 2010[Robinson et al, , 2014 and decline in the quantity of extrachromosomal MDV genomes [Kaschka-Dierich et al, 1979;Delecluse and Hammerschmidt, 1993].…”
mentioning
confidence: 99%
“…Precisely why these viruses have captured cellular telomere repeats and use these chromosomal sites for integration during latency is not known, but it is possible that telomeres provide a unique recombinogenic environment conducive for viral integration and mobilization during reactivation. For MDV, telomere integration enhances tumor formation (Greco et al, 2014). It is not yet clear whether these integrated viral genomes can reactivate efficiently to complete their viral productive cycles or if these integrations are pathogenic aberrations.…”
Section: Genome Maintenance Mechanismsmentioning
confidence: 99%
“…MDV integration can occur in all chicken chromosome classes, including macro-, intermediate- and micro-chromosomes without a preference for the either the p or q arm [ 22 ]. The presence of the virus genome in host telomeres has been confirmed by various techniques including fluorescent in situ hybridization (FISH) and pulsed-field gel electrophoresis (PFGE) [ 21 , 23 , 24 , 25 , 26 ]. Integration into host telomeres has also been shown for other herpesviruses, which will briefly be addressed within this review.…”
Section: Marek’s Disease Virus Integrationmentioning
confidence: 99%
“…This phenotype was comparable to the mutant viruses harboring the mutated TMR, indicating that the mTMR plays a major role in the MDV genome integration into host telomeres. In addition, it has recently been demonstrated that the sTMR has a dual function in the MDV life cycle [ 23 ]. Deletion of sTMR abrogated MDV replication, as these sequences serve as a spacer between the packaging signal pac-1 and the DR-1 cleavage site to ensure proper cleavage and packaging of the viral genome into the capsid.…”
Section: MDV Telomeric Repeatsmentioning
confidence: 99%